Explaining Entrepreneurial Success of SMEs Entrepreneurs: The Role of Entrepreneurial Characteristics - Prakash Kumar Gautam; Ram Bahadur Khadka (Pravaha, 2022)
Small and medium sized enterprises have significant role in sustainable economic growth and country. This study aims to investigate the entrepreneurial characteristics predicting entrepreneurial success of small and medium sized enterprises. Following analytical research design, this study collected data using structured questionnaire from 263 entrepreneur managers. Result revealed that entrepreneurial motivation, entrepreneurial self-efficacy, and risk-taking propensity have significant role in predicting entrepreneurial success of SMEs but refuted for entrepreneurial innovativeness. Moderating role of gender was examined in the study. The result advocates that the study contributes to the entrepreneurial competency theory and contributes for policy makers for entrepreneurial growth for sustainable development goals.